Division algebras and maximal orders for given invariants - Böckle, Gebhard; Gvirtz, Damián (LMS journal of computation and mathematics, 2016)
Brauer classes of a global field can be represented by cyclic algebras. Effective constructions of such algebras and a maximal order therein are given for Fq(t), excluding cases of wild ramification. As part of the construction, we also obtain a new description of subfields of cyclotomic function fields.